Bioinspired Fatty Acid Amide‐Based Slippery Oleogels for Shear‐Stable Lubrication. Issue 8 (24th January 2022) - Lee, Jaehyeon; Kim, Boram; Lee, Ji Woong; Hong, Chan Young; Kim, Gwang Hoon; Lee, Sang Joon
Abstract: Liquid‐repellent technology is an efficient means of energy‐saving and biofouling avoidance. However, liquid‐repellent surfaces suffer from inefficient lubricant retention under shear flow and fouling problem in marine environment. Here, the authors demonstrate a fatty acid amide (FAA)‐based oleogel for stable and sustainable lubrication in marine environment. The lubrication management of marine creatures is emulated in synthetic oleogels by incorporating solid (FAA) and liquid lubricants into the molecular meshes of polymeric networks, with the nature‐derived solid lubricant providing multifunctional synergistic effects with liquid oil molecules for slippery property and remarkable anti‐biofouling. The lubricant‐confining gel achieves shear‐stable lubricity with efficient oil management. The oleogel provides continued lubrication without biofouling for approximately 4 months in marine field tests. The gel design provides a new paradigm for sustainable and shear‐stable lubrication in marine environment. Abstract : A new shear‐stable lubrication strategy is proposed to be engineered at the molecular level, inspired by the lubricant management of marine creatures. The bioinspired lubricant confinement strategy enables efficient oil management through the synergetic effects of the solid and liquid lubricant molecules in the molecular meshes. The dual solid/liquid lubricant‐based gel system provides slippery properties with anti‐biofouling properties, enabling shear‐stable lubrication without biofouling for practical marine applications.